Concepts and concerns in remodeling swine facilities - Murphy, P. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Shall I remodel or burn it down? Determining an answer to this question requires careful consideration of construction costs and production goals. When considering a particular building - consider the following:
Keywords: Swine; Remodel; Swine facilities